Multicenter investigation of predictors to self-report vaccination and seroprotection against Hepatitis B among healthcare workers - Morcerf, Vivianne Lins Ebrahim; Lacet, Celina Maria Costa; Largura, Álvaro; Silva, Evanio da; Barbosa, Kevan Guilherme Nóbrega; Ferreira, Sonia Maria Soares; Abreu, Silvio Romero de Oliveira (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Objective: The Healthcare Workers (HCWs) are professionals with occupational exposure risk to Hepatitis B virus (HBV). Vaccination status has been widely explored; however, few investigations had confirmed the HBV immunity by serological test. Method: We performed a multicenter study based on a dual approach to understand the predictive factors of vaccination and seroprotection to HBV among HCWs. A cross-section design investigation was carried out among 371 workers from Alagoas state (Brazil); all of them from the public health service. Multiple Poisson Regression Models were constructed using vaccination and seroprotection as dependent factor. Results: The overall self-report of vaccination was 70.4% and the confirmation by immune response was 72.2%. Three predictive factors were associated with vaccination: education level; use of the PPE during work, and personal serological evaluation. Two predictive factors were associated with seroprotection: education level and use of the PPE during work. Conclusion: Our findings showed some evidence that almost one third of healthcare workers were not immune to HBV, and factors such as education and use of the protective equipment can predict the susceptibility to HBV.